2015
DOI: 10.1158/0008-5472.can-14-3790
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Parallel DNA Damage Response Pathways Optimizes Radiosensitization of Glioblastoma Stem-like Cells

Abstract: Glioblastoma is the most common form of primary brain tumor in adults and is essentially incurable. Despite aggressive treatment regimens centered on radiotherapy, tumor recurrence is inevitable and is thought to be driven by glioblastoma stem-like cells (GSC) that are highly radioresistant. DNA damage response pathways are key determinants of radiosensitivity but the extent to which these overlapping and parallel signaling components contribute to GSC radioresistance is unclear. Using a panel of primary patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(165 citation statements)
references
References 48 publications
9
155
1
Order By: Relevance
“…S2F). Moreover, we have previously shown that these GSCs display characteristic infiltrative growth pattern in intracranial in vivo model (29,30). Indeed, a significant inhibition of colony growth was observed in PME-1 depleted GSCs (E2 and R10 cell lines) treated with either STS or UCN-01 (Fig.…”
Section: Pme-1 Drives Resistance To Clinically Relevant Indolocarbazomentioning
confidence: 69%
“…S2F). Moreover, we have previously shown that these GSCs display characteristic infiltrative growth pattern in intracranial in vivo model (29,30). Indeed, a significant inhibition of colony growth was observed in PME-1 depleted GSCs (E2 and R10 cell lines) treated with either STS or UCN-01 (Fig.…”
Section: Pme-1 Drives Resistance To Clinically Relevant Indolocarbazomentioning
confidence: 69%
“…Mechanistic cellular studies indicate that dual inhibition of cell cycle checkpoints and DNA repair mechanisms yields the most effective radiosensitization of GBM stem-like cells and there is exciting potential to combine small molecule inhibitors of ATR with the PARP inhibitor compounds described above (22). Systemic toxicity is likely to be an issue in this context, especially if temozolomide is included in the therapeutic cocktail, but intelligent scheduling of DNA damage response inhibitors, along with judicious combination with targeted radiotherapy, should enable a beneficial therapeutic index to be achieved.…”
Section: Targeting the Atm And Atr Signaling Nodesmentioning
confidence: 99%
“…Accordingly, CSC have the potential to self-renew, differentiate and maintain tumour growth and repopulation following radio-or chemotherapy. Two models exist for the organisation of CSC: one that assumes a hierarchically organised system in which only a small proportion of tumour cells actually have any tumourigenic potential whilst most tumour cells are unable to induce tumours (Lapidot et al 1994;Al-Hajj et al 2003), and a clonal evolution model in which random changes enable subclones to emerge with new functions and treatment responses within the tumour. In fact, both models may have some merit and could coexist, assuming that clonal evolution may shape the make-up of the small proportion of stem-like cells (Maugeri-Sacca et al 2014).…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…However, as multiple DNA damage response pathways may be simultaneously upregulated in CSC, as shown in glioma stem cells, a multi-targeting approach involving combined inhibition of DNA repair and cell cycle checkpoint mechanisms may be a more promising strategy for overcoming CSC resistance (Signore et al 2014;Ahmed et al 2015).…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation